Do Investment Decisions Matter for Firm Value? An Empirical Analysis of Financial Firms - Yosua; Kuswanto, Randy (Indonesia Banking School, 2025)
This study examines the impact of investment decisions, dividend policy, profitability, and firm size on firm value in financial sector companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Employing a quantitative approach with purposive sampling, 25 financial companies were selected based on specific criteria, including consistent listing, dividend distribution, and financial reporting in Indonesian Rupiah. Classical assumption tests confirmed the validity of the regression model, and hypothesis testing was conducted using F-test and t-test. The findings reveal that profitability has a significant positive effect on firm value, while dividend policy and investment decisions do not exhibit a significant impact. Interestingly, firm size shows a significant negative effect, possibly due to regulatory pressures and post-pandemic operational challenges. These results highlight the dominant influence of regulatory compliance and investor focus on financial performance rather than expansion-oriented strategies. The adjusted R² value of 0.230 indicates that 23% of the variation in firm value is explained by the studied variables, suggesting that other factors outside the model may also significantly influence firm value.